Genetic Transformation of a Clinical (Genital Tract), Plasmid-Free Isolate of Chlamydia trachomatis: Engineering the Plasmid as a Cloning Vector - Wang, Yibing (Public Library of Science, 2013)
Our study had three objectives: to extend the plasmid-based transformation protocol to a clinical isolate of C. trachomatis belonging to the trachoma biovar, to provide “proof of principle” that it is possible to “knock out” selected plasmid genes (retaining a replication competent plasmid) and to investigate the plasticity of the plasmid. A recently developed, plasmid-based transformation protocol for LGV isolates of C. trachomatis was modified and a plasmid-free, genital tract C. trachomatis isolate from Sweden (SWFP-) was genetically transformed. Transformation of this non-LGV C. trachomatis host required a centrifugation step, but the absence of the natural plasmid removed the need for plaque purification of transformants. Transformants expressed GFP, were penicillin resistant and iodine stain positive for accumulated glycogen. The transforming plasmid did not recombine with the host chromosome. A derivative of pGFP::SW2 carrying a deletion of the plasmid CDS5 gene was engineered. CDS5 encodes pgp3, a protein secreted from the inclusion into the cell cytoplasm. This plasmid (pCDS5KO) was used to transform C. trachomatis SWFP-, and established that pgp3 is dispensable for plasmid function. The work shows it is possible to selectively delete segments of the chlamydial plasmid, and this is the first step towards a detailed molecular dissection of the role of the plasmid. The 3.6 kb β-galactosidase cassette was inserted into the deletion site of CDS5 to produce plasmid placZ-CDS5KO. Transformants were penicillin resistant, expressed GFP and stained for glycogen. In addition, they expressed β-galactosidase showing that the lacZ cassette was functional in C. trachomatis. An assay was developed that allowed the visualisation of individual inclusions by X-gal staining. The ability to express active β-galactosidase within chlamydial inclusions is an important advance as it allows simple, rapid assays to measure directly chlamydial infectivity without the need for plaquing, fluorescence or antibody staining.